Barriers and facilitators of medicines reconciliation at transitions of care in Ireland - a qualitative study - Grimes, Tamasine (My University, 2020)
Background: Medication error at transitions of care is common. The implementation of medicines reconciliation processes to improve this issue has been recommended by many regulatory and safety organisations. The aim of this study was to gain insight from healthcare professionals on the barriers and facilitators to the medicines reconciliation implementation process. Methods: Semi-structured interviews were conducted in Ireland with a wide range of healthcare professionals (HCPs) involved with medicines reconciliation at transitions of care. Thematic analysis was undertaken using an adaptation of a combined theoretical framework of Grol, Cabana and Sluisveld to classify the barriers and facilitators to implementation of medicines reconciliation. Results: Thirty-five participants were interviewed, including eleven community pharmacists (CPs), eight hospital pharmacists (HPs), nine hospital consultants (HCs), five general practitioners (GPs), and two non-consultant hospital doctors (NCHDs). Themes were categorized into barriers and facilitators. Barriers included resistance from existing professional cultures, staff interest and training, poor communication and minimal information and communications technology (ICT) support. Solutions (facilitators) suggested included supporting effective multidisciplinary teams, greater involvement of pharmacists in medicines reconciliation, ICT solutions (linked prescribing databases, decision support systems) and increased funding to provide additional (e.g. admission and discharge reconciliation) and more advanced services (e.g. community pharmacist delivered medicines use review). Conclusions: Medicines reconciliation is advocated as a solution to the known problem of medication error at transitions of care. This study identifies the key challenges and potential solutions that policy makers, managers and HCPs should consider when reviewing the practices and processes of medicines reconciliation in their own organisations.
PUBLISHED
Keywords: Medicines reconciliation; Patient safety; Qualitative research; Health plan implementation; Continuity of patient care/organization & administration; Inclusive Society; Medication Reconciliation; Medication safety; Patient safety; QUALITATIVE RESEARCH; transitions of care; Health